The Role of Digital Banking Services in the Success of Commercial Banks in Uzbekistan - Urinov Komil (Peerian Journals Publishing, 2022)
This article describes the digital services being implemented in the activities of commercial banks in Uzbekistan. The article analyzes the activities of traditional banks and new digital banks.
Keywords: Bank; digitization; TBS; Anorbank